Nitrogen Sensing Across Different Corn Growth Stages Using Soil Plant Analysis Development Meter - Lucas H. Suguiura; Leonardo L. Bosche; Luiz Felipe A. Almeida; Ignacio A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
The Soil Plant Analysis Development (SPAD) meter is a sensor widely utilized as an indirect method to monitor nitrogen (N) status in various crops. However, the sensor’s accuracy can be affected by environmental and crop-specific factors. This study aimed to investigate the utility of employing the SPAD to monitor N in corn leaves at different growth stages, using the Nitrogen Sufficiency Index (NSI). For this reason, a trial was conducted in Topeka, KS (US), during the 2023 growing season featuring twelve treatments with varied N levels, rates, and fertilization timings. The study analyzed the relationship between 1) SPAD meter readings and leaf N concentration (Nc), and 2) Nc, NSI, and corn grain yield at V6, V10, V14, and R1 crop growth stages. The Nc was positively correlated with grain yield at V14, particularly at R1 when Nc accounted for most yield variations. The results suggest that the NSI approach, implemented via the SPAD meter from the V10 growth stage onward, serves as an effective predictor for estimating the Nc.
Keywords: corn; nitrogen sensing; SPAD meter; nitrogen sufficiency index; leaf nitrogen concentration